Distribution and Status of Highland Mushrooms: A Study from Dolpa, Nepal - Devkota, Shiva (Journal of Natural History Museum, 2009)
This study comprises report on mycological exploration in 2006 at the most remote and highland district, Dolpa of Western Nepal. The study area was virgin for mushrooms study. Forty four species were collected, out of which 40 are new to the area. The collected species are parasitic, saprophytic and mycorrhizal associates' in habitat. Locally 22 and five species were used for culinary and medicinal values respectively. Cordyceps sinensis, Morchella conica, M. esculenta, Laetiporus sulphureus, Agaricus bisporus, Termitomyces clypeatus and Cantharellus cibarius are most popular and potential resources from the study sites. Key words: Caterpillar fungus; Dolpa; macrofungi; morels mushrooms; Nepal Journal of Natural History Museum Vol. 23, 2008 Page 51-59